THEORETICAL AND METHODOLOGICAL BASIS OF THE USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Masodikova , Zulfiyakhon; Eshonkulova , Motabar (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article analyzes the theoretical and methodological foundations of artificial intelligence (AI)–based approaches in foreign language teaching and their impact on educational effectiveness. In the context of modern digital education, AI technologies create opportunities to individualize the language learning process, organize adaptive learning, and provide immediate feedback. The results confirm that AI-based approaches have a positive effect on the development of learners’ communicative and linguistic competencies, as well as on the formation of independent learning skills. The article substantiates the necessity of methodologically grounded integration of artificial intelligence technologies into the process of foreign language teaching.